Neuronal Representation of the Saccadic Timing Signals in Macaque Lateral Intraparietal Area. (28th July 2017) - Zhou, Yang; Liu, Yining; Wu, Si; Zhang, Mingsha
Abstract: Primates frequently make saccades direct fovea on interesting objects to receive acute visual information. However, saccade displaces the images on retina and disrupts the visual constancy. One possible mechanism to retain visual constancy is by integrating the presaccadic and postsaccadic visual information right at the time of saccade, which makes the timing of saccade crucial. So far, the saccadic timing signals have been found only in the subcortical regions, for example, the cerebellum and superior colliculus, but not in the neocortex. Here we report 2 types of saccadic timing signals in macaque lateral intraparietal area (LIP). First, many presaccadic response neurons started to decline activity either right around the start (saccade-on-decay) or the end (saccade-off-decay) of saccades. Notably, the time difference between saccade-off-decay and saccade-on-decay was highly correlated with the mean duration of saccades but not with the individual ones, and both saccade-off-decay and saccade-on-decay were better aligned with saccade end than saccade start–reflecting prediction. Second, the peak activity plateau of a group of postsaccadic response neurons was highly correlated with the actual duration of saccade–reflecting reality. While the predicted timing signals might facilitate the integration of visual information across saccades in LIP, the actual duration signals might calibrate the prediction errors.